A paradox indeed: description of genitalia and clarification of the subtribal classification of Pachyonychis paradoxus Clark and Pachyonychus paradoxus Melsheimer (Coleoptera: Chrysomelidae: Galerucinae: Alticini) - van Roie, Martijn; Clark, Shawn; Konstantinov, Alexander; Furth, David; Linzmeier, Adelita M. (Zootaxa, 2023)
Pachyonychis paradoxus Clark, 1860 and Pachyonychus paradoxus Melsheimer, 1847 are two species of Alticini whose strikingly similar names have led to significant confusion in the past. Recent study of American Oedionychina Chapuis, 1875 raised doubts about the validity of the subtribal placement of Pachyonychis Clark. Although general characteristics put this genus in Oedionychina, other features, especially the unusual shape of the pronotum, suggested that this monotypic genus would belong in Monoplatina Chapuis, 1875 instead. To collect evidence for the validity of its current placement, we compared external and genitalic morphology of both species to other members of Monoplatina and Oedionychina. Here we present images and descriptions of female genitalia for both species and male genitalia of Pachyonychus paradoxus Melsheimer, to our knowledge the first of their kind, and we conclude that the evidence supports the current subtribal placement of these two genera. Lectotypes are designated for both Pachyonychis paradoxus Clark and Pachyonychus paradoxus Melsheimer.